Pelatihan Penulisan Buku Ajar pada Guru Sekolah Menengah Pertama di Kota Magelang - Mira Fitriana; Yusuf Wahyu Setiya Putra; Cisilia Sundari (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
The limited competence of Junior High School (SMP) teachers in Magelang City in developing contextual textbooks is a key issue hindering the achievement of locally relevant learning. Teachers primarily rely on commercial textbooks that often lack accommodation for specific regional issues and lack guidelines for independent writing. This community service aimed to enhance the knowledge and skills of SMP teachers in Magelang City in compiling textbooks that meet the standards of the Merdeka Curriculum and include local content. The method employed was participatory training combined with blended mentoring over six weeks, involving 30 teachers from five schools representing various general subjects. The implementation began with a theoretical workshop on standard textbook structure, followed by intensive mentoring sessions. The results indicate a significant increase in participants' understanding of the textbook framework, with 90% of teachers independently capable of creating concept maps and chapter outlines. Crucially, 75% of participants successfully produced at least one draft chapter of a textbook rich in local content (history, culture, and geography of Magelang). This success not only increases the professional capacity of teachers but also directly impacts the availability of more relevant and specific learning resources for students, supporting the contextual implementation of the Merdeka Curriculum.